Functional polypeptide-modified nanocomposite magnetic beads and method and application thereof for detecting β-secretase
Through the nanocomplex magnetic beads modified with functional polypeptides, the complexity and inefficiency of the existing β-secretase detection methods are solved, and the rapid and sensitive detection of β-secretase is achieved, with high sensitivity and anti-interference ability.
Patent Information
- Application Number
- CN202411989760.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing β-secretase activity detection methods such as ELISA and FRET probe methods have problems such as expensive antibodies, poor repeatability, cumbersome operation and long analysis cycles. The selection requirements for the FRET probe method are high, which limits its application in the field of inhibitor screening.
A nanocomposite magnetic bead modified with functional polypeptide was prepared, and nanocomposite magnetic beads were prepared through layer-layer assembly technology to make their composition and microstructure more design-oriented. The fluorescein-labeled functional polypeptide was modified on the surface of the nanocomposite magnetic beads through the interaction between Co2+ or Ni2+ and His tags.
Fast and sensitive detection of β-secretase is achieved, and the detection sensitivity and anti-interference ability are improved. The nanocomposite magnetic beads have small particle size, high magnetic response, large specific surface area, and high biomolecular load. They are suitable for fluorescence/magnetic biosensing detection and biofluorescence imaging.
Smart Images

Figure CN119400538B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanocomposite material preparation and analysis and detection, and specifically relates to a nanocomposite magnetic bead modified with a functional polypeptide and a method and application thereof for detecting beta-secretase. Background Art
[0002] With the aging process in my country, Alzheimer's disease (AD), which has a high incidence and great harm in the elderly population, has seriously threatened the lives and health of the people. The main pathological feature of AD is the deposition of β-amyloid protein (Aβ) in the patient's brain to form amyloid plaques. β-Secretase (BACE1) can cleave amyloid precursor protein (APP) to generate Aβ, and is the rate-limiting enzyme for Aβ production. Therefore, BACE1 has always been considered an important target for the treatment of AD. In addition, many recent studies have also shown that BACE1 plays an important role in the body's metabolism, vascular function and immune function abnormalities. Abnormally elevated BACE1 can directly or indirectly accelerate the aging of the body and promote the development of aging-related diseases (such as cardiovascular and cerebrovascular diseases, diabetes and cancer). Therefore, monitoring of β-secretase activity and screening of its inhibitors are of great significance in the biomedical field.
[0003] At present, the main methods for detecting β-secretase activity and screening its inhibitors are enzyme-linked immunosorbent assay (ELISA) and fluorescence resonance energy transfer (FRET) probe method. Although ELISA and FRET probe methods are effective, they both have certain difficulties in practical applications. The ELISA method has the disadvantages of expensive antibodies, poor repeatability, cumbersome operation and long analysis cycle, while the FRET probe method has the disadvantages of high excitation wavelengths of some easily labeled fluorescent groups often coinciding with the absorption wavelengths of many small drug molecules, which leads to high requirements for the selection of fluorescent donors and acceptors of FRET probes, limiting its application in the field of inhibitor screening. Therefore, in order to meet the needs of practical applications, it is urgent to develop a new method for detecting β-secretase activity that is highly versatile, highly sensitive, simple and rapid.
[0004] Magnetic nanobiomaterials are nanomaterials with multiple functions. They have the characteristics of nanomaterials, such as small particle size and large specific surface area, as well as the special magnetic guidance, superparamagnetism and relaxation properties of magnetic materials. They can aggregate and locate in a constant magnetic field, and absorb electromagnetic waves to generate heat in an alternating magnetic field. Therefore, they are widely used in biological separation, targeted drug delivery, magnetic resonance imaging, magnetic thermal therapy, biosensing, etc. The magnetic fluorescent nanobioprobe obtained by modifying the surface of magnetic nanobiomaterials with fluorescent labeled biomolecules combines magnetic and fluorescent properties. Its stable fluorescent signal and good specific recognition ability can realize sensitive detection of biomolecules. At the same time, it can also realize rapid "separation-dispersion" cycle operation under the action of an external magnetic field and can be reused.
[0005] Based on the above discussion, the present invention prepares a composite nanomagnetic bead modified with a functional polypeptide for β-secretase, which can detect β-secretase quickly and sensitively, and has potential application value and important research significance in the biomedical field. Summary of the invention
[0006] In view of the above technical problems, the object of the present invention is to provide a functional polypeptide modified nanocomposite magnetic bead, the chemical composition of the nanocomposite magnetic bead is: ferroferric oxide nanoclusters are used as magnetic cores, the surface of the magnetic core is coated with a silica shell layer, the surface of the shell layer is connected with an ethylenediaminetetraacetic acid modification layer, and the modification layer is chelated with metal ions Co 2+ or Ni 2+ , the functional peptide labeled with fluorescein Cy5 and the metal ion Co 2+ or Ni 2+ The coupling is loaded on the surface of the nanocomposite magnetic beads; the amino acid sequence of the fluorescent Cy5 labeled functional polypeptide is:
[0007] ① Cys-Gly-Gly-Ser-Ser-Glu-Val-Asn-Leu-Asp-Ala-Glu-Phe-Ser-Ser-Gly-Leu-His-His-His-His-His-His; (SEQ ID No. 1)
[0008] ② Lys-Thr-Glu-Glu-Ile-Ser-Glu-Val-Asn-Leu-Asp-Ala-Glu-Phe-Arg-His-Asp-Lys-Cys-His-His-His-His-His-His; (SEQ ID No. 2)
[0009] ③ Cys-Leu-Gly-Gly-Glu-Val-Asn-Leu-Asp-Ala-Glu-Phe-Gly-Gly-Leu-His-His-His-His-His-His; (SEQ ID No. 3)
[0010] ④[(His-His-His-His-His-His)4Lys]-Gly-Gly-Pro-Pro-Pro-Pro-Pro-Pro-Pro-Pro-Gly-Glu-Val-Asn-Leu-Asp-Ala-Glu-Phe-Asp-Asp-Lys-Gly-Gly-Asp-Asp-Asp-NH2 (SEQ ID No.4) shown in any one.
[0011] The second object of the present invention is to provide a method for preparing the functional polypeptide-modified nanocomposite magnetic beads, comprising the following steps:
[0012] (1) Preparation of Fe3O4 nanoclusters by solvent method;
[0013] (2) using the ferroferric oxide nanoclusters prepared in step (1) as magnetic cores, and preparing silicon dioxide-coated ferroferric oxide nanocluster particles by an ultrasonic-assisted sol-gel method;
[0014] (3) dispersing the silica-coated ferroferric oxide nanocluster particles prepared in step (2) in methanol, and then adding glacial acetic acid and sodium N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid to form a mixed solution, wherein the mass ratio of glacial acetic acid to sodium N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid is 1:2 to 1:10, reacting for 1 to 3 hours under the assistance of ultrasound with a power of 150 to 300 W, and washing with acetone and deionized water after the reaction is completed to obtain EDTA-modified silica-coated ferroferric oxide nanocluster particles;
[0015] (4) The EDTA-modified silica-coated ferroferric oxide nanoclusters prepared in step (3) are ultrasonically dispersed in water, and an aqueous solution of NiCl2 or CoCl2 is added, wherein the mass ratio of the EDTA-modified silica-coated ferroferric oxide nanoclusters to NiCl2 or CoCl2 is 1:10 to 1:100. After the mixed solution is reacted for 1.5 to 3 hours, it is washed three times with deionized water to obtain the metal ion Ni 2+ or Co 2+ Chelating nanomagnetic beads;
[0016] (5) Dispersing the metal ion chelated nanomagnetic beads prepared in step (4) in a PBS solution, adding a functional polypeptide aqueous solution with a concentration of 5 to 15 µmol / L, incubating the reaction at 37°C, and magnetically separating the nanomagnetic beads; washing the nanomagnetic beads 3 to 5 times with a PBS solution until the fluorescence intensity of the washing solution approaches zero, and the obtained magnetic beads are nanocomposite magnetic beads modified with functional polypeptides.
[0017] Preferably, the specific steps of preparing ferroferric oxide nanoclusters by the solvent method in step (1) are as follows:
[0018] First, weigh ferric chloride and dissolve it in ethylene glycol, then add sodium acetate and deionized water, and stir until completely dissolved to form a mixed solution, wherein the mass ratio of ferric chloride, sodium acetate and deionized water is 1:3:1. The mixed solution is added into a reactor, and the program is set to heat to 140 ~ 170 ℃ and keep warm for 1.5 ~ 3 h, then heat to 180 ~ 220 ℃ and keep warm for 2 ~ 8 h. The pressure during the whole reaction process is 0.01 ~ 0.1 Pa. After the reaction is completed, take out the precipitate in the reactor and wash it with acetone and anhydrous ethanol respectively to obtain ferroferric oxide nanoclusters.
[0019] Preferably, the specific steps of preparing silicon dioxide-coated ferroferric oxide nanocluster particles by the ultrasound-assisted sol-gel method in step (2) are as follows:
[0020] First, a certain amount of ferroferric oxide nanocluster particles are taken, and a mixed solvent of deionized water and anhydrous ethanol with a volume ratio of 1:5 to 4:5 is added, and ultrasonic dispersion is uniform; then concentrated ammonia water and tetraethyl orthosilicate are added in an ice water bath environment, wherein the volume ratio of tetraethyl orthosilicate to concentrated ammonia water is 1:10 to 1:20, and ultrasonic reaction is carried out at a power of 180 to 360 W for 20 to 60 min. After the reaction is completed, the particles are washed twice with anhydrous ethanol and deionized water respectively, to obtain silica-coated ferroferric oxide nanocluster particles.
[0021] The third object of the present invention is to provide a method for detecting β-secretase using the functional polypeptide-modified nanocomposite magnetic beads for non-diagnostic purposes, wherein the method comprises the following steps:
[0022] (1) Establishment of a standard curve for β-secretase detection: To establish a standard curve for β-secretase detection: First, a certain amount of functional polypeptide-modified nanocomposite magnetic beads is dispersed in an acetic acid-sodium acetate buffer solution, and then different concentrations of β-secretase standard solutions are added. The reaction is incubated at 37°C. After the reaction is completed, magnetic separation is performed, and the supernatant is collected and its fluorescence intensity is detected. Then, a linear fit is performed based on the β-secretase concentration and the characteristic value of the fluorescence intensity signal to establish a standard curve for β-secretase detection.
[0023] (2) Detection of β-secretase content in the sample: Add the sample solution containing β-secretase to the PBS buffer solution of the functional polypeptide-modified nanocomposite magnetic beads, incubate, measure the characteristic value of the fluorescence intensity signal of the solution, substitute it into the standard curve obtained in step (1), and calculate the β-secretase content in the sample.
[0024] Preferably, the concentration of the acetic acid-sodium acetate buffer solution in step (1) is 20 mmol / L, the pH is 4.5-6.0, the concentration of the functional polypeptide-modified nanocomposite magnetic beads is 0.2-1.0 mg / mL, and the reaction time is 60-120 min.
[0025] The fourth object of the present invention is to provide the use of the functional polypeptide modified nanocomposite magnetic beads or the functional polypeptide modified nanocomposite magnetic beads prepared by the preparation method in detecting β-secretase for non-diagnostic purposes.
[0026] The fifth objective of the present invention is to provide the use of the functional polypeptide-modified nanocomposite magnetic beads in screening β-secretase inhibitors.
[0027] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention provides a functional polypeptide modified nanocomposite magnetic bead, wherein the nanocomposite magnetic bead is prepared by first preparing silica-coated ferroferric oxide nanoclusters as basic magnetic beads, then using a one-step carboxylation to prepare ethylenediaminetetraacetic acid (EDTA) modified nanomagnetic beads, and then utilizing the coordination effect of the three carboxyl groups of EDTA with metal ions to chelate Co on the surface of the magnetic beads. 2+ or Ni 2+ , and finally through Co 2+ or Ni 2+ The functional polypeptide labeled with fluorescein is modified on the surface of the nanocomposite magnetic beads through the interaction with the His tag. The nanocomposite magnetic beads are prepared by layer-by-layer assembly technology, making their composition and microstructure more designed. At the same time, it can also achieve directional coupling between the magnetic beads and the polypeptide chains, effectively expose the recognition sites of the functional polypeptides, and enhance the efficiency of the enzymatic reaction between the functional polypeptides on the surface of the magnetic beads and β-secretase, thereby improving the sensitivity of detection.
[0028] (2) The method for preparing nanocomposite magnetic beads provided by the present invention can functionalize the base magnetic beads with multiple carboxyl groups through a one-step modification with EDTA, thereby effectively increasing the carboxyl density on the surface of the magnetic beads and facilitating the next step of modification of the base magnetic beads.
[0029] (3) The method for preparing nanocomposite magnetic beads provided by the present invention, in which the magnetic bead intermediate obtained during the preparation process - metal ion Ni 2+ or Co 2+ Chelated nanomagnetic beads (Fe3O4NCs@SiO2-EDTA-M 2+ ), the surface metal ion Ni 2+ or Co 2+ The content of the magnetic beads is high, and they can be coupled with different His-tagged proteins and antibodies, and have a wide range of applications. In addition, the preparation reaction conditions of the magnetic beads are mild, which is conducive to large-scale preparation and has a certain universality.
[0030] (4) The nanocomposite magnetic beads provided by the present invention have small particle size, high magnetic response, large specific surface area, high biomolecule loading capacity, and both magnetic and fluorescent properties, and can play an important role in fluorescent / magnetic biosensor detection and bioluminescent imaging.
[0031] (5) The method for detecting β-secretase by using functional polypeptide-modified nanocomposite magnetic beads provided by the present invention has a detection linear range of 2.5 ng / mL to 800 ng / mL and a detection limit of 0.62 ng / mL. This method has the advantages of high sensitivity, strong anti-interference ability, low background signal, and can be magnetically separated and reused. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Example 1 Flow chart of preparing functional polypeptide modified nanocomposite magnetic beads;
[0033] Figure 2 Transmission electron microscopy (TEM) images of Fe3O4NCs@SiO2 nanoparticles prepared in Example 1, wherein (a) is a TEM image of the entire Fe3O4NCs@SiO2 nanoparticles coated with silicon dioxide, and (b) is a magnified image of a Fe3O4NCs@SiO2 nanoparticle;
[0034] Figure 3 Infrared spectrum characterization of EDTA-modified nanomagnetic beads prepared in Example 1;
[0035] Figure 4 Conductometric titration curve of carboxyl content of EDTA-modified nanomagnetic beads prepared in Example 1;
[0036] Figure 5 Example 1 Preparation of Ni 2+ X-ray photoelectron spectroscopy (XPS) of chelated nanomagnetic beads, where (a) is Ni 2+ Full spectrum of chelated nanomagnetic beads, (b) is the Ni2p fine spectrum;
[0037] Figure 6 Example 1 Preparation of Ni 2+ Magnetic hysteresis loop (VSM) diagram of chelated nanomagnetic beads;
[0038] Figure 7 Fluorescence microscopy image of the functional polypeptide-modified nanocomposite magnetic beads prepared in Example 1;
[0039] Figure 8 Transmission electron microscopy image of Fe3O4NCs@SiO2 nanomagnetic beads prepared in Example 2;
[0040] Fig. 9 Different buffer systems when Fe3O4NCs@SiO2 is connected with EDTA;
[0041] Fig.10 Co 2+ X-ray photoelectron spectrum of chelated nanomagnetic beads, where (a) is Co 2+ Full spectrum of chelated nanomagnetic beads, (b) is the Co2p fine spectrum;
[0042] Fig.11 The fluorescence stability of nanocomposite magnetic beads prepared by functional peptides labeled with different fluorescein;
[0043] Fig.12 Comparison of β-secretase detection by nanocomposite magnetic beads modified with different peptide chains under the same conditions;
[0044] Fig.13 Effects of different pH buffer systems on the detection of β-secretase activity;
[0045] Fig.14 The fluorescence spectrum changes of the detection system after adding different concentrations of β-secretase;
[0046] Fig.15 The response linear curve of the detection system after adding different concentrations of β-secretase to the reaction;
[0047] Fig.16 Selectivity of functional peptide-modified nanocomposite magnetic beads for detecting β-secretase;
[0048] Fig.17 The inhibitory efficiency of β-secretase inhibitors was tested using functional peptide-modified nanocomposite magnetic beads. DETAILED DESCRIPTION
[0049] In order to make the technical means, creative features, purpose and effect of the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments. The following examples are only used to illustrate the technical solution of the present invention but not to limit it. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
[0050] In the following examples, the methods used are all conventional methods;
[0051] In the following examples, the reagents and consumables used can be purchased from the market.
[0052] It should be noted that in the following examples, the composition of the PBS buffer solution is as follows: pH=6.0, 20 mM PBS containing 300 mM NaCl, 0.05% Tween-20 and 10 mM imidazole.
[0053] Example 1. Preparation of functional polypeptide modified nanocomposite magnetic beads
[0054] The preparation process of functional peptide modified nanocomposite magnetic beads is as follows Figure 1 As shown, the specific steps are as follows:
[0055] (1) Preparation of Fe3O4 NCs
[0056] Weigh 0.34 g of FeCl3·6H2O, add it to 60 mL of ethylene glycol, then add 0.9 g of NaAC·3H2O and 0.3 mL of deionized water, stir until completely dissolved and add it to a high-temperature and high-pressure reactor. Set the program to heat to 160°C for 3 hours, then heat to 200°C for 2 hours, so that the pressure during the entire reaction process is maintained between 0.01-0.1 Pa. After the reaction is completed, take out the precipitate in the reactor and wash it with anhydrous ethanol and deionized water three times respectively, to obtain ferroferric oxide nanocluster particles (Fe3O4NCs).
[0057] (2) Preparation of silica-coated magnetic beads (Fe3O4NCs@SiO2)
[0058] Take 35 mg of magnetic nanoparticles Fe3O4NCs, add 20 mL of anhydrous ethanol and 12 mL of deionized water, and ultrasonically disperse them at a power of 30% for 10 min to make them fully dispersed in the solvent; in addition, add 2 mL of concentrated ammonia water and 100 μL of tetraethyl orthosilicate (TEOS) in an ice water bath environment, and ultrasonicate them at a power of 220W for 40 min. After the reaction is completed, wash them twice with anhydrous ethanol and deionized water respectively, and then obtain silica-coated iron oxide nanocluster particles (Fe3O4NCs@SiO2), the transmission electron microscope image of which is shown in the figure. Figure 2 As shown in (a), Figure 2 (b) is an enlarged image of a Fe3O4NCs@SiO2 nanoparticle. As can be seen from the figure, the Fe3O4NCs@SiO2 magnetic beads are core-shell structures with an average particle size of about 160 nm and a shell thickness of about 14 nm. The magnetic core Fe3O4 nanocrystals (Fe3O4NCs) are tiny Fe3O4 nanocrystals assembled into loose spherical particles. The Fe3O4NCs@SiO2 nanoparticles show good dispersion and uniformity.
[0059] (3) Preparation of EDTA-modified magnetic beads (Fe3O4NCs@SiO2-EDTA)
[0060] The Fe3O4NCs@SiO2 prepared in (2) was dispersed in 50 mL of methanol, 50 μL of glacial acetic acid was added, and then 400 μL of N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid sodium salt (TMS-EDTA) was added. Ultrasonic reaction was carried out at 300 W (on for 5 s, off for 5 s) at 30°C for 2 h. The mixture was washed twice with acetone and deionized water, respectively, to obtain Fe3O4NCs@SiO2-EDTA. The infrared comparison of Fe3O4NCs@SiO2-EDTA and Fe3O4NCs@SiO2 is shown in Figure 2. Figure 3 As shown in the figure, we can see that 1385 cm -1 An obvious peak appeared on the left and right, which was the symmetric stretching peak of the carboxylate group, indicating that EDTA had been successfully connected to the surface of Fe3O4NCs@SiO2.
[0061] In addition, in order to measure the carboxyl content on the surface of Fe3O4NCs@SiO2-EDTA, we conducted a conductivity titration test. The test method is: add a small amount of pH=2 HCl solution to the Fe3O4NCs@SiO2-EDTA magnetic bead solution, add pH=12 NaOH solution drop by drop under stirring, and record the change of conductivity value with the addition of NaOH, draw a relationship between the amount of added NaOH and conductivity, and then calculate the carboxyl content. The results are shown in Figure 4 As shown, it can be calculated that the carboxyl content on the surface of Fe3O4NCs@SiO2-EDTA nanomagnetic beads can reach 320.3 μmoL / g.
[0062] (4) Metal ion Ni 2+ Chelated nanoparticles (Fe3O4@NCsSiO2-EDTA-Ni 2+ )
[0063] Take 300 μL of 20 mg / ml Fe3O4NCs@SiO2-EDTA nanoparticle dispersion in a 5 mL EP tube, add 4 mL NiCl2 solution (concentration is 1 mol / L), mix and react for 2 h, and wash with deionized water 3 times to obtain Fe3O4NCs@SiO2-EDTA-Ni 2+ .Fe3O4NCs@SiO2-EDTA-Ni 2+ The X-ray diffraction (XPS) pattern is as follows Figure 5 As shown, where (a) is Ni 2+ The full spectrum of chelated nanoparticles, (b) is the Ni2p fine spectrum; Figure 5 As can be seen in (b), Ni2+ Successfully chelated on the surface of Fe3O4@NCsSiO2-EDTA nanomagnetic beads.
[0064] In addition, we also used a vibrating sample magnetometer to measure the Ni 2+ The magnetic properties of the chelated nanoparticles are shown in the hysteresis loop at room temperature. Figure 6 As shown in the figure, it can be seen that after layer-by-layer coating and surface treatment with ferroferric oxide nanoclusters (Fe3O4NCs) as the magnetic core, the nanocomposite magnetic beads still show a high magnetic response, with a saturation magnetization intensity of 57 emu / g, and its coercive force is close to zero, showing superparamagnetism.
[0065] (5) Preparation of functional peptide-modified nanocomposite magnetic beads
[0066] The Fe3O4@NCsSiO2-EDTA-Ni 2+ Dispersed in aqueous solution, a cy5-labeled functional polypeptide was designed, and the specific amino acid sequence was [(His-His-His-His-His)4Lys]-Gly-Gly-Pro-Pro-Pro-Pro-Pro-Pro-Pro-Pro-Pro-Gly-Glu-Val-Asn-Leu-Asp-Ala-Glu-Phe-Asp-Asp-Lys-(Cy5)-Gly-Gly-Asp-Asp-Asp-NH2 (SEQ ID No.4, it should be noted that in the sequence table, only the amino acid sequence of the straight chain portion is included: Gly-Gly-Pro-Pro-Pro-Pro-Pro-Pro-Pro-Pro-Pro-Gly-Glu-Val-Asn-Leu-Asp-Ala-Glu-Phe-Asp-Asp-Lys-(Cy5)-Gly-Gly-Asp-Asp-Asp-NH2, while the amino acid sequence of the branched chain portion is replaced by X, specifically X is [(His-His-His-His-His-His)4Lys]), which is prepared into a 100 μM aqueous solution for use.
[0067] Take 70 μL Fe3O4NCs@SiO2-EDTA-Ni 2+(Concentration is 5 mg / mL) magnetic bead dispersion in an EP tube, add 550 μL PBS (20 mM PBS, pH=6.0) for washing, magnetic separation, and aspirate the supernatant. Add 480 μL PBS solution again to wash the nanocomposite magnetic beads, magnetic separation, and aspirate the supernatant. Add 600 μL of the above PBS buffer solution, mix well, and then add 9 μL of 100 μM peptide solution, incubate the reaction at 37 °C for 2 h. After the reaction is completed, wash with PBS solution, magnetic separation, and aspirate the supernatant. Wash until the fluorescence intensity in the supernatant is basically zero, and the functional peptide-modified nanocomposite magnetic beads are obtained. Figure 7 This is a fluorescence microscope image of the nanocomposite magnetic beads modified with functional polypeptides after washing. The image shows that the polypeptide chains are successfully modified on the surface of the nanocomposite magnetic beads.
[0068] Example 2. Preparation of nanocomposite magnetic beads modified with functional polypeptides
[0069] The difference from Example 1 is:
[0070] Step (1) Weigh 0.68 g of FeCl3·6H2O, add it to 60 mL of ethylene glycol, then add 1.8 g of NaAC·3H2O and 0.6 mL of deionized water, stir until completely dissolved and add it to a high temperature and high pressure reactor. Set the program to heat to 160 °C for 3 h, then heat to 200 °C for 2 h, so that the pressure during the entire reaction process is maintained between 0.01 and 0.1 Pa. After the reaction is completed, take out the precipitate in the reactor and wash it with anhydrous ethanol and deionized water three times respectively.
[0071] Then, 35 mg of magnetic nanoparticles Fe3O4NCs were taken, 20 mL of anhydrous ethanol and 12 mL of deionized water were added, and ultrasonic dispersion was performed. Then, 2 mL of concentrated ammonia and 200 μL of tetraethyl orthosilicate (TEOS) were added in an ice-water bath environment, and ultrasonication was performed for 40 min at a power of 300 W. After the reaction was completed, the particles were washed twice with anhydrous ethanol and deionized water, respectively. The transmission electron microscopy image of the obtained Fe3O4NCs@SiO2 is shown in the figure. Figure 8 As shown in the figure, it can be seen that the average particle size of the magnetic beads prepared in Example 2 is about 350 nm, which is significantly larger than the magnetic beads in Example 1, and the particle size distribution is not very uniform.
[0072] Example 3. Preparation of nanocomposite magnetic beads modified with functional polypeptides
[0073] The difference from Example 1 is:
[0074] The solvent added in step (3) of this embodiment is ethanol, and other conditions remain unchanged. The infrared results are as follows: Fig. 9As shown in the figure, it can be seen that when the reaction system is methanol, 1385cm -1 There is an obvious peak at 1700 cm -1 The peak at is the stretching vibration absorption peak of the C=O double bond, which is the absorption peak of the carboxyl group. Fig. 9 The results show that methanol is a more suitable solvent than ethanol when carboxyl groups are connected.
[0075] Example 4. Preparation of Nanocomposite Magnetic Beads Modified with Functional Peptides
[0076] The difference from Example 1 is:
[0077] In step (4), Fe3O4NCs@SiO2-EDTA nanoparticles are connected to Co 2+ , take 300 uL of 20 mg / ml Fe3O4NCs@SiO2-EDTA nanoparticle dispersion in a 5 mL EP tube, add 4 mL CoCl2 solution (concentration is 1 mol / L), mix and react for 2 h. After the reaction is completed, wash it with deionized water three times to obtain Fe3O4NCs@SiO2-EDTA-Co 2+ .Fe3O4NCs@SiO2-EDTA-Co 2+ The detailed spectrum results of X-ray photoelectron spectroscopy are as follows Fig.10 As shown in the figure, it can be seen that Co 2+ Successfully chelated on the surface of Fe3O4NCs@SiO2-EDTA.
[0078] Example 5. Preparation of functional polypeptide modified nanocomposite magnetic beads
[0079] In order to investigate the fluorescence stability of nanocomposite magnetic beads prepared by using functional polypeptides labeled with different fluoresceins in an acidic buffer system over time, this example was specially conducted. The preparation process of the nanocomposite magnetic beads in this example is the same as that in Example 1, except that the fluoresceins used to label the functional polypeptides are fluorescein isothiocyanate (FITC) and rhodamine B, respectively. The specific experimental results are shown in FIG. Fig.11 As shown. From the results, it can be seen that the nanocomposite magnetic beads modified with anthocyanin fluorescent dye fluorescein (Cy5) labeled functional polypeptide have the best fluorescence stability in the acidic buffer system. Since many literatures show that β-secretase has the strongest activity in acidic buffer systems, the functional polypeptide labeled with fluorescein Cy5 is suitable for preparing nanocomposite magnetic beads to detect β-secretase.
[0080] Example 6. Preparation of functional polypeptide modified nanocomposite magnetic beads
[0081] The process of preparing functional polypeptide modified nanocomposite magnetic beads in this example is the same as that in Example 1, except that the amino acid sequence of the functional polypeptide used is: Cys-Leu-(Aib)-Gly-Gly-Glu-Val-Asn-Leu-Asp -Ala-Glu-Phe-Gly-Gly-(Aib)-Leu-His-His-His-His-His (SEQ ID No. 3), and the His tag of the functional polypeptide is inserted into the N-terminus of the polypeptide chain, i.e., the "straight" peptide chain. Compared with the "dendritic" peptide chain in Example 1, the results are as follows: Fig.12 (No. 1 is a straight polypeptide chain, No. 2 is a dendritic polypeptide chain) as shown in Fig.12 It can be seen that after reacting with the same concentration of β-secretase, the fluorescence intensity of the "dendritic" polypeptide chain modified nanocomposite magnetic beads is higher than that of the straight chain, indicating that the "dendritic" polypeptide chain is better than the "straight chain" polypeptide modified on the surface of the nanocomposite magnetic beads, and it can undergo enzymatic hydrolysis reaction with β-secretase, and its performance is more stable.
[0082] Example 7. Preparation of functional polypeptide modified nanocomposite magnetic beads
[0083] The process of preparing functional polypeptide modified nanocomposite magnetic beads in this example is the same as that in Example 1, except that the amino acid sequence of the functional polypeptide used is: Cys-Gly-Gly-Ser-Ser-Glu-Val-Asn-Leu-Asp-Ala-Glu-Phe-Ser-Ser-Gly-Leu-His-His-His-His-His-His (SEQ ID No. 1).
[0084] Example 8. Preparation of Nanocomposite Magnetic Beads Modified with Functional Peptides
[0085] The process of preparing functional polypeptide modified nanocomposite magnetic beads in this example is the same as that in Example 1, except that the amino acid sequence of the functional polypeptide used is: Lys-Thr-Glu-Glu-Ile-Ser-Glu-Val-Asn-Leu-Asp- Ala-Glu-Phe-Arg- His-Asp-Lys-Cys-His-His-His-His-His-His (SEQ ID No. 2).
[0086] Example 9: Application of a functional polypeptide modified nanocomposite magnetic beads 1
[0087] This example is to investigate the effect of different pH buffer systems on the detection of β-secretase by composite nanomagnetic beads modified with functional polypeptides. First, the nanocomposite magnetic beads prepared in Example 1 were used to detect 20mM acetic acid-sodium acetate buffer systems with different pH values of 4.5, 5.0, and 6.0, respectively. Then, 0.1% Triton and the same amount of β-secretase were added, and the reaction was vortexed for 2 h at a reaction temperature of 37°C. After the reaction was completed, magnetic separation was performed, and the supernatant of the sample was aspirated for fluorescence testing. The results are shown in Figure 2. Fig.13 As shown in the figure, it can be seen that the pH value of the buffer system has a great influence on the detection of β-secretase by nanocomposite magnetic beads. When pH=5.0, the detection performance of the nanocomposite magnetic beads is optimal, which may be due to the better stability and high enzyme activity of β-secretase at this time.
[0088] Example 10: Application of a functional polypeptide modified nanocomposite magnetic beads 2
[0089] In order to verify that the prepared functional polypeptide-modified nanocomposite magnetic beads can detect β-secretase, different amounts of β-secretase were added to the functional polypeptide-modified nanocomposite magnetic beads prepared in Example 1, and the fluorescence in the supernatant after the reaction was completed was finally detected. The specific operation steps are as follows:
[0090] First, the functional peptide-modified nanocomposite magnetic beads were dispersed in a solution of acetic acid-sodium acetate mixture (pH=5.0, 0.1% Triton), vortexed for 2 h, and the reaction temperature was 37 °C. After the reaction was completed, magnetic separation was performed and the supernatant of each sample was collected. The specific experimental results are shown in Figure 2. Fig.14 As shown in the figure, different volumes of β-secretase were added to make the final reaction concentrations: 0 ng / mL, 2.5 ng / mL, 10 ng / mL, 50 ng / mL, 100 ng / mL, 200 ng / mL, 400ng / mL, 600 ng / mL, and 800 ng / mL. Fig.14 It can be seen that when the concentration of β-secretase gradually increases in the range of 0 ~ 800 ng / mL, the fluorescence intensity of the detection system also increases, which indicates that the nanocomposite magnetic beads modified with the functional peptide have a good response to changes in the concentration of β-secretase. In addition, Fig.15 The standard curve of β-secretase is shown in Figure 1. The concentration change of β-secretase and the change of fluorescence intensity of the detection system show a good linear relationship. The linear range of β-secretase detection is 2.5 ng / mL ~ 800 ng / mL, the detection limit is 0.62 ng / mL, and the linear equation is y=7.372+0.249x. The correlation coefficient R 2 =0.985.
[0091] Example 11: Anti-interference ability of functional polypeptide-modified nanocomposite magnetic beads in detecting β-secretase
[0092] This example is to investigate the anti-interference ability of functional polypeptide-modified nanocomposite magnetic beads in detecting β-secretase. The detection steps are the same as those in Example 10, except that: the target β-secretase to be detected in the detection system is replaced by glucose oxidase (Glucose), trypsin (Trypsin), human immunoglobulin G (IgG), thrombin (Prothrombin), and bovine serum albumin (BSA) that may exist in the actual sample, respectively. After the reaction is completed, the change in fluorescence intensity in the supernatant is measured. The specific results are shown in FIG. Fig.16 shown.
[0093] from Fig.16 It can be seen that when anti-interference substances that may coexist with β-secretase exist in the detection system, only β-secretase can obviously cause changes in fluorescence response, and other interference substances do not have obvious changes. This shows that the magnetic fluorescent composite probe of the present invention has a strong anti-interference ability and is suitable for the detection of β-secretase in complex environments.
[0094] Example 12: Feasibility of screening inhibitors using functional peptide-modified nanocomposite magnetic beads
[0095] In order to investigate the feasibility of screening β-secretase inhibitors by using functional polypeptide-modified nanocomposite magnetic beads, the activity of β-secretase was first inhibited by using a known inhibitor (β-secretase Inhibitor IV), and then reacted with the functional polypeptide-modified nanocomposite magnetic beads prepared in Example 1, and finally observed the changes in the fluorescence spectrum in the reaction system. The specific steps are as follows:
[0096] β-secretase was mixed with inhibitors (β-secretase Inhibitor IV) of different concentrations and incubated. 20 mM acetic acid-sodium acetate buffer at pH 5.0 was added to the resulting solution to make the volume reach 600 μL. The solution was vortexed and reacted for 2 h at a reaction temperature of 37°C.
[0097] After the reaction is completed, the fluorescence intensity in the supernatant is tested, and the results are as follows: Fig.17 As shown in the figure, as the concentration of inhibitor IV gradually increased, the fluorescence intensity in the supernatant decreased, indicating that inhibitor IV had a good inhibitory effect on β-secretase. The inhibition efficiency was calculated according to the formula [ I F0 - I Fi / I F0 ×100%], where I F0represents the initial enzyme activity (the fluorescence intensity of the detection system when only β-secretase is added), I Fi Represents the residual enzyme activity (the fluorescence intensity of the detection system when β-secretase is added after the inhibitor has reacted with it). The inhibitory ability of the inhibitor is expressed as IC 50 To describe, IC 50 The concentration of the inhibitor required to inhibit the enzyme activity by half is given by the IC value of the inhibitor IV. 50 The value is 20 nM, which is consistent with the IC value provided by the supplier of β-secretase inhibitors. 50 The above results show that the functional polypeptide modified nanocomposite magnetic beads provided by the present invention can be used for the screening of β-secretase inhibitors and have a certain universality.
[0098] In summary, the preparation method of the functional polypeptide-modified nanocomposite magnetic beads provided by the present invention is simple, and the prepared nanocomposite magnetic beads have a good response to β-secretase. It can be used for the detection of β-secretase, has the advantages of high sensitivity, strong anti-interference ability, and small background signal, and can be used for the analysis and detection of samples. The linear range of its detection of β-secretase is 2.5 ng / mL~800 ng / mL, and the detection limit is 0.62 ng / mL. It has important application potential in the early diagnosis, treatment and drug development of Alzheimer's disease (AD).
[0099] Finally, it should be noted that the above is only a preferred embodiment of the present invention and does not limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A nanocomposite magnetic bead modified with a functional polypeptide, characterized in that: The chemical composition of the nanocomposite magnetic beads is as follows: a ferroferric oxide nanocluster is used as a magnetic core, a silicon dioxide shell is coated on the surface of the magnetic core, an ethylenediaminetetraacetic acid modification layer is connected to the surface of the shell, and a metal ion Co is chelated on the modification layer. 2+ or Ni 2+ , the functional peptide labeled with fluorescein Cy5 and the metal ion Co 2+ or Ni 2+ The coupling is loaded on the surface of the nanocomposite magnetic beads; the amino acid sequence of the fluorescent Cy5 labeled functional polypeptide is: ① Cys-Gly-Gly-Ser-Ser-Glu-Val-Asn-Leu-Asp-Ala-Glu-Phe-Ser-Ser-Gly-Leu-His-His-His-His-His-His; ②Lys-Thr-Glu-Glu-Ile-Ser-Glu-Val-Asn-Leu-Asp-Ala-Glu-Phe-Arg-His-Asp-Lys-Cy s-His-His-His-His-His-His; ③Cys-Leu-Gly-Gly-Glu-Val-Asn-Leu-Asp-Ala-Glu-Phe-Gly-Gly-Leu-His-His-His-His-His-His; ④Any one of [(His-His-His-His-His-His)4Lys]-Gly-Gly-Pro-Pro-Pro-Pro-Pro-Pro-Pro-Pro-Gly-Glu-Val-Asn-Leu-Asp-Ala-Glu-Phe-Asp-Asp-Lys-Gly-Gly-Asp-Asp-Asp-NH2.
2. The method for preparing the functional polypeptide-modified nanocomposite magnetic beads according to claim 1, characterized in that: The steps include: (1) Preparation of FeO nanoclusters by solvent method; (2) using the ferroferric oxide nanoclusters prepared in step (1) as magnetic cores, and preparing silicon dioxide-coated ferroferric oxide nanocluster particles by an ultrasonic-assisted sol-gel method; (3) dispersing the silica-coated ferroferric oxide nanocluster particles prepared in step (2) in methanol, and then adding glacial acetic acid and sodium N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid to form a mixed solution, wherein the mass ratio of glacial acetic acid to sodium N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid is 1:2 to 1:10, reacting for 1 to 3 hours under the assistance of ultrasound with a power of 150 to 300 W, and washing with acetone and deionized water after the reaction is completed to obtain EDTA-modified silica-coated ferroferric oxide nanocluster particles; (4) The EDTA-modified silica-coated ferroferric oxide nanoclusters prepared in step (3) are ultrasonically dispersed in water, and an aqueous solution of NiCl2 or CoCl2 is added, wherein the mass ratio of the EDTA-modified silica-coated ferroferric oxide nanoclusters to NiCl2 or CoCl2 is 1:10 to 1:
100. After the mixed solution is reacted for 1.5 to 3 hours, it is washed three times with deionized water to obtain the metal ion Ni 2+ or Co 2+ Chelating nanomagnetic beads; (5) dispersing the metal ion chelating nanomagnetic beads prepared in step (4) in a PBS solution, adding a functional polypeptide aqueous solution with a concentration of 5 to 15 μmol / L, incubating the reaction at 37° C., and magnetically separating the nanomagnetic beads; washing the nanomagnetic beads 3 to 5 times with a PBS solution until the fluorescence intensity of the washing solution approaches zero, and the obtained magnetic beads are nanocomposite magnetic beads modified with functional polypeptides.
3. The preparation method according to claim 2, characterized in that: The specific steps of preparing ferroferric oxide nanoclusters by the solvent method described in step (1) are as follows: First, weigh ferric chloride and dissolve it in ethylene glycol, then add sodium acetate and deionized water, and stir until it is completely dissolved to form a mixed solution, wherein the mass ratio of ferric chloride, sodium acetate and deionized water is 1:3:1, and add the mixed solution into a fully automatic high-temperature and high-pressure reactor, set the program to first heat to 140-170°C and keep it warm for 1.5-3h, then heat to 180-220°C and keep it warm for 2-8h, the pressure during the whole reaction process is 0.01-0.1Pa, after the reaction is completed, take out the precipitate in the reactor and wash it with acetone and anhydrous ethanol respectively, so as to obtain ferroferric oxide nanoclusters.
4. The preparation method according to claim 2, characterized in that: The specific steps of preparing silicon dioxide-coated ferroferric oxide nanocluster particles by the ultrasound-assisted sol-gel method in step (2) are as follows: First, a certain amount of ferroferric oxide nanocluster particles are taken, and a mixed solvent of deionized water and anhydrous ethanol with a volume ratio of 1:5 to 4:5 is added, and ultrasonic dispersion is uniform; then concentrated ammonia water and tetraethyl orthosilicate are added in an ice water bath environment, wherein the volume ratio of tetraethyl orthosilicate to concentrated ammonia water is 1:10 to 1:20, and ultrasonic reaction is carried out at a power of 180 to 360 W for 20 to 60 minutes. After the reaction is completed, the particles are washed twice with anhydrous ethanol and deionized water respectively, so as to obtain silica-coated ferroferric oxide nanocluster particles.
5. Use of the functional polypeptide-modified nanocomposite magnetic beads according to claim 1 in screening β-secretase inhibitors.
Citation Information
Patent Citations
Fluorescent magnetic nano-composite and preparation method and application thereof
CN112029728A
Magnetic fluorescent composite probe for detecting matrix metalloproteinase-2 as well as preparation method and application of magnetic fluorescent composite probe
CN113045672A